Structural bioinformatics-based identification of putative plant based lead compounds for Alzheimer Disease Therapy. (February 2019) - Borah, Kasmika; Sharma, Sanchita; Silla, Yumnam
Abstract: Plant based lead compounds have been historically incredible as a source of therapeutic agents for various complex disorders including Alzheimer's disease (AD). AD is one of the leading neurodegenerative disorder in which the underlying risk factors remain largely unclear and presently, there is no disease modifying treatment available. Despite its potential, to date only few compounds have entered for clinical trials. Herein, we described the identification of plant based lead compounds for treatment of AD through an integrative approach of pharmacokinetics and structure bioinformatics approach. In particular we performed screening of lead compounds from 3 traditional medicinal plants namely Withania somnifera, Bacopa monnieri and Morus alba, which are known to have potential for treatment of neurodegenerative disease. We retrieved a total of 210 plant based compounds of which 21 compounds were screened based on their pharmacokinetic properties. Further, Docking study against 7 known AD associated targets were carried out to identify the binding sites and direct interacting residues. In addition we investigate the stable and reliable binding mechanism of top such plant compounds against 3 targets through molecular docking followed by Molecular Dynamic(MD) simulation. The results obtained in the study revealed that 3 drug compounds namely Morusin (MRSN), Withanone (WTHN) and 27-Hydroxywithanolide B (HWTHN) were identified as putative lead compounds against mono amine oxidase (MAOB), Beta-secretase 1(BACE1) and phosphodiesterase 4D.